2017
DOI: 10.5021/ad.2017.29.4.462
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Profile of Patients with Psoriasis in Korea: A Nationwide Cross-Sectional Study (EPI-PSODE)

Abstract: BackgroundPsoriasis is an immune-mediated, chronic inflammatory disease affecting multiple aspects of patients' lives. Its epidemiology varies regionally; however, nationwide epidemiologic data on psoriasis depicting profile of Korean patients has not been available to date.ObjectiveTo understand nationwide epidemiologic characteristics and clinical features of adult patients with psoriasis visited university hospitals in Korea.MethodsThis multicenter, non-interventional, cross-sectional study recruited 1,278 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
4
30
2
Order By: Relevance
“…The EPI‐PSODE study was a nationwide, multicenter, non‐interventional, cross‐sectional study examining the epidemiology of psoriasis in Korea conducted by the Korean Society for Psoriasis (KSP). The 25 centres participating in the study were university hospitals located across the country.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPI‐PSODE study was a nationwide, multicenter, non‐interventional, cross‐sectional study examining the epidemiology of psoriasis in Korea conducted by the Korean Society for Psoriasis (KSP). The 25 centres participating in the study were university hospitals located across the country.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, patient‐reported outcomes related to HRQoL, including DLQI, were collected in a nationwide study that described the epidemiologic characteristics and clinical features of patients with psoriasis in Korea . We sought to ascertain the relationship between clinical characteristics and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first, largest and longest observational cohort study unveiling direct association between psoriasis and an increased risk of ASCVD comorbidities among Asians. Considering the relatively lower prevalence of psoriasis in Asian countries including Korea (0.3–0.4% prevalence rate), the results from our large‐scale cohort enabled us to assess the significant risk for ASCVD in Korean psoriatic patients from more than 1.7 million enrolled participants.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is an immune‐mediated inflammatory skin disorder characterized by erythematous scaly plaques of chronic nature . It affects approximately 1–5% of the Western population, but its prevalence in the Asian population is reported to be lower than 1% . The major underlying immunopathogenesis of psoriasis consists of the immune cell‐derived interleukin (IL)‐23–IL‐17 cytokine axis which mediates dysregulated hyperproliferation and differentiation of keratinocytes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation